Higher Education in Latin America : The International Dimension - de Wit, Hans (Washington, DC: World Bank, 2012)
This book compares internationalization issues, trends, and opportunities in higher education in selected Latin American countries at the institutional, national, and regional levels. It addresses the specific elements of the internationalization process, such as mobility, curriculum, linkages, and networks. Rather than investigating these issues in detail, however, it examines them as part of a more comprehensive overview of policies, programs, and activities at all three levels. The volume examines these elements and the broader process of internationalization in the context of the overall development of higher education. It analyzes the potential contribution of internationalization to institution and nation building, examining such issues as the implications of trade, new forms of delivery, new providers, and the relevance of accreditation and quality assurance for higher education and their international dimensions.